Integrated probing the influence of dye acceptor with several electron withdrawing groups for dye-sensitized solar cells. (1st January 2020) - Sun, Zhu-Zhu; Feng, Shuai; Ding, Wei-Lu
Graphical abstract: Two acceptors with suitable amounts of electron withdraw groups for fluorene-based sensitizer can be screened by balancing various performances in dye-sensitized solar cells. Highlights: A theoretical design of novel fluorine–based organic analogues. Different acceptors with several electron withdrawing groups are considered to compare various properties. Increased electron withdrawing groups on both acceptors raised the optical and kinetics properties. S3 and S5 dye with more electron withdrawing groups was screened as a candidate. Abstract: In order to explore the influence of diverse acceptors with varying amounts of electron withdrawing groups on the organic dye in dye-sensitized solar cell (DSCs), a series of JF419 organic analogues with several cyano groups (CN) on acceptor were engineered. By performing theoretical studies on these investigated dyes and the corresponding dye/(TiO2 )38 complexes, two benzoic acid units (benzothiadiazole benzoic acid and vinyl benzoic acid) with more -CNs were identified as alternative acceptors for DSCs. Particularly, S3 and S5 dyes exhibited impressive red-shift in spectra (ca. 77 nm for S3 and 48 nm for S5 compared with JF419), more accessible charge separation state and large driving force for dye regeneration (ΔGreg = 0.51 eV for S3 and ΔGreg = 0.61 eV for S5). According to quantifying the charge transfer (CT) on semiconductor surface, it found that the growing electron withdrawing groups on acceptor can strengthen the interaction between dyes and TiO2 and provide favorable conditions for electron injection. A brilliant balance between the electron injection time (τ = 6.8 fs for S3 and τ = 7.3 fs for S5) and the electron-hole recombination distance (r = 20.5 Å for S3 and r = 19.2 Å for S5) could be acquired for S3 and S5 dyes. Synthetically, introducing electron withdrawing groups on acceptor for organic dyes is a valid approach for gaining great performance of DSCs.